The Presumed Double-Apse Church in the Monastery of San Venerio on the Island of Tino (La Spezia) : Reconsidering the Context Thanks to New Archaeological Data (Fenestella. Inside Medieval Art, 2023)
The origin of medieval churches with two apses has long been a matter of investigation. Upon the rocky isle of Tino, emerging from the gulf of Spezia, once  a monastery under the title of San Venerio did stand. Today, its area preserves ruins believed to belong to a double-apse church. Previous studies had possibly detected a single-hall church, dating back to the sixth or seventh century, to which a second nave should have been added during the ninth century. In consideration of such early dates, it was claimed that the monument was the prototype of double-apse churches across the old diocese of Luni.New excavations carried out in 2021 and 2022 by the Archaeological Superintendence of Genoa and La Spezia have led to a significant revision of the Tino’s complex. First, the architectural plan does not provide evidence of any double-apse church. Furthermore, the masonry suggests the first half of the eleventh century.Remarkably enough, in that period, some descendants of the Marquis Obertus invited a monastic community to settle on the renewed island. Therefore, the structure in question may have been a commemorative chapel (memoria), erected by the Benedictines to mark the supposed place of hermitage and death of Venerius: a respected Saint whose cult the monks wanted to be revived in the interest of themselves and their supporters.
Keywords: Benedictine Monasteries; San Venerio; Obertenghi Marquises; Double-apse church